Pemahaman Keluarga Terhadap Individu Dengan Hambatan Kejiwaan Di Wilayah Kerja Puskesmas Peundeuy Kabupaten Garut - Perceka, Andhika Lungguh; Suryawantie, Tanti; Islamiawati, Intan (Universitas Pahlawan Tuanku Tambusai, 2024)
Patients with acute psychiatric constraints in Garut Regency in 2022 amounted to 4,054. Improper treatment and handling of patients with psychiatric obstacles can worsen the patient's condition. This study aims to understand family perceptions of care for ODGJ. This research uses a qualitative approach using a phenomenological approach. The population obtained was 40 patients who faced mental barriers by determining the elements of the review study that described the place of research, time, individuals, perceptions, demographics, and activities. The respondents used in this study were 3 (three) family members who have family members with severe ODGJ. The result obtained from this study is that the family's perception of ODGJ treatment is to bring in psychics, smart people, or ustad. This is due to the strong assumption that the cause of ODGJ is witchcraft or possession by spirits, so they decide to do supernatural treatment, in addition to other factors such as cost, as well as the lack of information about mental health programs at health service centers. It is concluded that the three informants believe that mental obstacles are caused by witchcraft and possession by spirits. Medical treatment becomes the last alternative in the treatment method for ODGJ, although in the end the informants can feel a better change after seeing a doctor compared to being taken to a shaman and an ustad.